Queensland Family Cohort: a study protocol. Issue 6 (24th June 2021) - Borg, Danielle; Rae, Kym; Fiveash, Corrine; Schagen, Johanna; James-McAlpine, Janelle; Friedlander, Frances; Thurston, Claire; Oliveri, Maria; Harmey, Theresa; Cavanagh, Erika; Edwards, Christopher; Fontanarosa, Davide; et al.
Abstract : Introduction: The perinatal–postnatal family environment is associated with childhood outcomes including impacts on physical and mental health and educational attainment. Family longitudinal cohort studies collect in-depth data that can capture the influence of an era on family lifestyle, mental health, chronic disease, education and financial stability to enable identification of gaps in society and provide the evidence for changes in government in policy and practice. Methods and analysis: The Queensland Family Cohort (QFC) is a prospective, observational, longitudinal study that will recruit 12 500 pregnant families across the state of Queensland (QLD), Australia and intends to follow-up families and children for three decades. To identify the immediate and future health requirements of the QLD population; pregnant participants and their partners will be enrolled by 24 weeks of gestation and followed up at 24, 28 and 36 weeks of gestation, during delivery, on-ward, 6 weeks postpartum and then every 12 months where questionnaires, biological samples and physical measures will be collected from parents and children. To examine the impact of environmental exposures on families, data related to environmental pollution, household pollution and employment exposures will be linked to pregnancy and health outcomes. Where feasible, data linkage of state and federal government databases will be used to follow the participants long term. Biological samples will be stored long term for future discoveries of biomarkers of health and disease. Ethics and dissemination: Ethical approval has been obtained from the Mater Research Ethics (HREC/16/MHS/113). Findings will be reported to (1) QFC participating families; (2) funding bodies, institutes and hospitals supporting the QFC; (3) federal, state and local governments to inform policy; (4) presented at local, national and international conferences and (5) disseminated by peer-review publications.